Modelling green organic field effect transistors from common biodegradable materials. (2023) - Siva Prasad, C.P.; Abhinav, T.; Predeep, P.
Abstract: A device that is fully green provides great advantages in terms of increased flexibility and biocompatibility. Organic field effect transistors (OFETs) offer high application potential in biomedical and allied fields, and developing suitable models for the simulation analysis of the OFETs is essential for their large-scale production. Here an attempt has been made to model some green OFETs using extracted data from experimental reports. Modeling and simulation of three different p-type semiconductor-based low voltage OFETs are undertaken. Two of the modelled devices used albumen and silk as dielectric materials. One of the devices is made with HD 230 paper as the substrate. It has been found that the compact model provided a nice fit with the experimental characteristics when used with the genetic algorithm for parameter extraction.